Challenges and Strategies in Education for Black Communities in Europe: A Scholarly Exploration - Emilia Elsa (GoAcademica Research & Publishing, 2023)
This scholarly article investigates the intricate landscape of education for Black communities in Europe, shedding light on the multifaceted challenges they encounter while delineating a comprehensive array of strategies to foster educational equity and inclusivity. In the backdrop of Europe's rich historical tapestry, marked by immigration waves, colonial legacies, and persistent racial biases, this study delves into the nuances of Black individuals' educational experiences, aiming to contribute to a more equitable and just educational milieu.